Atorvastatin for prevention of disease progression and hospitalisation in liver cirrhosis: protocol for a randomised, double-blind, placebo-controlled trial. Issue 1 (23rd January 2020) - Kimer, Nina; Grønbæk, Henning; Fred, Rikard Gøran; Hansen, Torben; Deshmukh, Atul Shahaji; Mann, Mathias; Bendtsen, Flemming
Abstract : Introduction: Patients with liver cirrhosis are often diagnosed late and once complications are present, the 2-year survival is 50%. Increasing evidence supports systemic inflammation and metabolic dysfunction in the hepatic stellate cell as key drivers of progression of cirrhosis. However, there is no registered medication, that targets inflammation and cellular dysfunction in the liver. Methods and analysis: In a randomised double-blind and placebo-controlled trial with atorvastatin for liver cirrhosis, we aim to investigate clinical endpoints of survival, hospitalisations and safety, but also exploratory endpoints of genomics and protein functions in the liver. Ethics and dissemination: There is no registered medication that actively prevents development of complications or systemic inflammation in liver cirrhosis. All patients continue regular clinical management during the trial period. Atorvastatin has been on the market for several years with a safety profile that is acceptable even in patients with liver disease. A beneficial effect of atorvastatin on clinical outcomes in cirrhosis will provide cheap and effective causal treatment for chronic liver disease. The trial is registered by the Danish Data Protection Agency (P-2019–635) and approved by the Danish Medicines Agency (EudraCT 2019-001806-40) and the Scientific Ethics Committee of the Capital Region of Denmark (H-19030643) before initiation. Reporting of the trial will follow the Consolidated Standards of Reporting Trials guidelines for reporting of randomised clinical trials. Trial registration number: The trial is registered in clinicaltrials.gov (NCT04072601 ) and in clinicaltrialsregister.eu (EudraCT 2019-001806-40) (Pre-results).